2011
DOI: 10.1021/jz1016872
|View full text |Cite
|
Sign up to set email alerts
|

When the Heterogeneous Appears Homogeneous: Discrepant Measures of Heterogeneity in Single-Molecule Observables

Abstract: Supercooled liquids demonstrate stretched exponential relaxations consistent with the presence of spatially heterogeneous dynamics. Many experimental results are consistent with this picture, but differences in experimental approach may lead to different conclusions about the degree of heterogeneity in a given system. Here, we investigate whether observables accessible with single molecule (SM) approaches are consistent with each other and with ensemble measurements. In particular, the distribution of rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…As discussed by Kaufman and coworkers, temporal heterogeneity of individual clusters may be greater on time scales outside our dynamic range of a few hours [13] spanned by our data. Near the bulk glass transition T g , kinetically facilitated models do not predict such a neat partitioning into CRR-to-CRR vs.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…As discussed by Kaufman and coworkers, temporal heterogeneity of individual clusters may be greater on time scales outside our dynamic range of a few hours [13] spanned by our data. Near the bulk glass transition T g , kinetically facilitated models do not predict such a neat partitioning into CRR-to-CRR vs.…”
mentioning
confidence: 58%
“…We imaged individual CRRs at metallic glass surfaces while ramping their temperature, obtaining real-time movies of their temperature-dependent dynamics. We studied a Fe 78 B 13 Si 8 alloy (asreceived 25.4 μm thick MetGlas® SA1 samples from MetGlas Inc., Conway SC, USA) with a glass transition temperature of T g = 780 K. Samples were degassed for 8 hours at 373 K and cleaned using 2 keV argon ion sputtering with a dose of ~1 to 10×10 16 ions/cm 2 . The surface composition analyzed by X-ray photoelectron spectroscopy was very similar to the bulk.…”
mentioning
confidence: 99%
“…Recent experiments and simulations showed that when the rotational correlation function U (t) was averaged over many molecules in different regions, U (t) was stretched exponential, i.e., U (t) ∼ exp[−(t/τ ) β ] with 0 < β < 1 [2,9,14,15]. The stretched-exponential form of U (t) is considered a clear indication of dynamic heterogeneity [2,9,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Second, photobleaching of the probe molecule limits the dynamic range in time: low light intensities extend the time window, but also require larger time bins to collect sufficient signal. Last and most disturbing, sampling noise-noise due to measuring a finite number of relaxations-is large and has seemed to be unavoidable [25][26][27][28].…”
mentioning
confidence: 99%